Children's Perceptions of Parental Mediation on Internet Use - Ulfa, Aliya; Agustiani, Hendriati; Qodariah, Laila; Jatnika, Ratna (Penerbit Goodwood, 2023)
Purpose: In this study, parental mediation is explained through the perception of children about their parents’ behavior. Methods: This study used a non-experimental descriptive method and described the following four strategies: active co-use, interaction restriction, technical restriction, and monitoring. The measurement tool used was a questionnaire on children’s perceptions of parental mediation. Data were collected from 240 children aged 9–12 years from two elementary schools. Results: The results showed that children perceived their parents to use the strategy of active co-use and interaction restriction at a moderate level, and monitoring at a low level. In the strategy of technical restriction, the data show that most children perceived that their parents did not use technical means to restrict internet use. Conclusions: Children perceived their parents as moderately involved in guiding and restricting Internet use, but with limited monitoring and minimal use of technical restrictions. This highlights the need for more balanced mediation strategies. Limitations: This study relied solely on children's perceptions. Future research should collect data from parents and children for comparative purposes. Contribution: This study contributes on the perception of children of Parental Mediation on Internet Use